COMMAND AND ORDER SPEECH ACTS IN THE MURDER CASE REPORT OF JUDGE JAMALUDDIN - Safreni, Fifi; Suhadi, Jumino; Manugeren, M. (Universitas Islam Sumatera Utara (UISU), 2024)
This study applies Searle's speech act theory, as outlined in Levinson (1983), to analyze directive speech acts in the high-profile murder case of Judge Jamaluddin. The research specifically examines how commands and orders issued by the main perpetrator, Zuraida Hanum, influenced her accomplices, M. Jefri Pratama and M. Reza Pahlevi, to commit premeditated murder. Using a qualitative descriptive method, data were sourced from the Medan District Court decision, which includes the defendants’ recorded utterances. The study categorizes directive speech acts based on the speaker's knowledge, intentions, and power dynamics, focusing on how Zuraida's directives were central to executing the crime. Findings reveal that command speech acts were not only pivotal in compelling the accomplices to act but also demonstrated the manipulation and influence wielded by the speaker. This research highlights the importance of speech act analysis in uncovering the linguistic mechanisms behind criminal behavior and underscores its potential applications in forensic linguistics and legal investigations.